USE OF POINT-OF-CARE ULTRASOUND (POCUS) IN THE ASSESSMENT OF FLUID RESPONSIVENESS: PRACTICAL APPLICATIONS AND METHODS - Fuchs, Luan Caimar; Aimi, Bruna Turra; Hatisuka, Felipe Romão; Zampieri, José Henrique Gorgone; Caro, Jaime Javier Garcia; de Souza, Kelen Marques; Gonçalves, Lucas Braun; Zanata, João Marcello Fernandes; Girardi, Júnior; Calore, Maria Eduarda Faraldo; Bez, Filippo Fabi; Rocha, Adriano Pereira; et al. (Seven Editora, 2026)
Fluid responsiveness assessment is essential in the management of critically ill patients, as inappropriate fluid administration is associated with adverse outcomes. In this context, point-of-care ultrasound (POCUS) has emerged as a key tool for hemodynamic monitoring, enabling dynamic bedside evaluation. This study is a structured critical narrative review analyzing 18 studies published between 2015 and 2025, identified through PubMed/MEDLINE, Scopus, and Web of Science databases. Ultrasound-based methods evaluated included left ventricular outflow tract velocity-time integral (LVOT VTI), passive leg raising (PLR), and indices derived from the inferior and superior vena cava. The findings demonstrate the superiority of dynamic over static parameters, with the combination of VTI and PLR representing the most consistent approach. In contrast, vena cava indices show greater variability and context-dependent limitations, while emerging methods such as carotid flow assessment require further validation. In conclusion, no single method is universally applicable, and an integrated, context-based approach is essential, with POCUS playing a central role in clinical decision-making.